Winning market leadership :strategic market planning for technology-driven businesses / Adrian B Ryans, Roger More, Donald Barclay, Terry Deutscher - More, Roger
Strategic marketing planning in technology-intensive businesses (e.g. , computers, telecommunications, software, biotechnology, semiconductors, and pharmaceuticals) is more complex and unmanageable than in most other businesses, traditionally taking up huge amounts of management time and producing plans that are quickly obsolete